THE EFFECT OF SALES PROMOTION ON CUSTOMER PURCHASING DECISIONS - Ramadhan, Rafy; Muhyi, Herwan Abdul; Muttaqin, Zaenal (Journal of Management Small and Medium Enterprises (SMEs), 2025)
There is an abundance of potential in Indonesia's food and beverage economy, but the Covid-19 pandemic conditions have prompted a significant change in consumer behavior, namely from direct purchases to digital purchases. The Cloud Kitchen concept is an option because it focuses on providing online food and beverage delivery services (online food & drink delivery). This is used by Ayam Bang Dava (ABD) to attract consumers and encourage purchases from online consumers who are basically interested in the promotional offers offered. This study aims to determine the effect of sales promotion on the purchasing decisions of Ayam Bang Dava (ABD) customers in Bandung Raya. The research method used is quantitative, verification and uses surveys as a data collection tool. Purposive sampling was a method when selecting the sample to target only Ayam Bang Dava (ABD) customers in Bandung Raya, with a total of 115 respondents. This study analyzes sales promotion variables through sales promotion tools conducted by Ayam Bang Dava (ABD), including bundles/bonus packs, price-offs, and event marketing. Purchasing decision variables are evaluated through aspects of product selection, brand selection, dealer selection, time and amount of purchase, and payment method. This study used simple linear regression analysis, coefficient of determination, and hypothesis testing to determine the existence of an influence. The results showed that the sales promotion carried out by ABD had an effect on the purchasing decisions of ABD customers in Bandung Raya. The value of the coefficient of determination obtained is 31%, which shows that the sales promotion variable can explain the purchase decision variable by 31%, and the remaining 69% is explained by other variables. Keywords: Purchase Decision; Sales Promotion; Online Food Delivery Service